Diversity and biological activity of fungal endophytes of Zingiber officinale Rosc. with emphasis on Aspergillus terreus as a biocontrol agent of its leaf spot. (January 2022) - Gupta, Suruchi; Choudhary, Malvi; Singh, Baljinder; Singh, Ravail; Dhar, Manoj K.; Kaul, Sanjana
Abstract: Leaf spot of ginger caused by Colletotrichum gloeosporioides is considered as a phytopathological constraint in the cultivation of ginger that has led to the economic loss of this valuable spice. Fungal endophytes serve as potent biocontrol agents for disease management because of their ability to colonize the same ecological niche similar to that of phytopathogen. The present study embarks on the isolation and identification of endophytic fungi from leaves and rhizomes of Zingiber officinale Rosc. A total of 563 endophytic fungal isolates were isolated which were grouped into 12 species belonging to 8 genera based on morphological characters and Internal Transcribed Spacers (ITS) sequence analysis. Among all the isolates, Aspergillus terreus possessed significant bioactivity profile and was subjected to bioassay guided fractionation. Various chromatographic and spectral analysis techniques led to the isolation and identification of an active molecule terrein. The purified compound displayed noteworthy antibacterial, antifungal and cytotoxic activities. Considering the antibacterial, cytotoxic and biocontrol potential of the fungus it could serve as a promising candidate in the field of agriculture and pharmaceutical industry. This is the first report on the biocontrol potential of fungal endophyte Aspergillus terreus and its bioactive metabolite terrein, against ginger leaf spot phytopathogen, C. gloeosporioides . Therefore, benefit of embracing such beneficial microorganism would be helpful in minimizing the use of agrochemicals and making agriculture more productive and sustainable. Further, terrein isolated from the A. terreus deserves special attention for its ability to serve as antimicrobial and anticancer agent. Graphical abstract: Image 1 Highlights: Isolation and identification of fungal endophytes from Zingiber officinale . Aspergillus terreus was the most potent endophyte with noteworthy bioactivities. Terrein was characterized as an active compound from fungal endophyte A. terreus . First report of A. terreus and terrein as biocontrol agent against C. gloeosporioides . Low IC50 value of terrein against colon cell lines.